Identification of aberrantly methylated differentially expressed genes and pro-tumorigenic role of KIF2C in melanoma - Huang, Chun-Hui; Han, Wei; Wu, Yi-Zhu; Shen, Guo-Liang (Frontiers in Genetics, 2022)
Background: Skin Cutaneous Melanoma (SKCM) is known as an aggressive malignant cancer that could be directly derived from melanocytic nevi. However, the molecular mechanisms underlying malignant transformation of melanocytes and melanoma tumor progression remain unclear. Increasing research showed significant roles of epigenetic modifications, especially DNA methylation, in melanoma. This study focused on the identification and analysis of methylation-regulated differentially expressed genes(MeDEGs) between melanocytic nevus and malignant melanoma in genome-wide profiles. Methods: The gene expression profiling datasets (GSE3189 and GSE114445) and gene methylation profiling datasets (GSE86355 and GSE120878) were downloaded from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) and differentially methylated genes (DMGs) were identified. MeDEGs were obtained by integrating the DEGs and DMGs. Functional enrichment analysis were performed. STRING and Cytoscape were used to describe protein-protein interaction network. Furthermore, survival analysis was implemented to select the prognostic hub genes. Next, we conducted gene set enrichment analysis. To validate, SKCM cell culture and lentivirus infection was performed to reveal the expression of KIF2C. Patients and specimens were collected and immunohistochemistry staining was conducted. Results: We identified 237 hypomethylated, upregulated genes and 182 hypermethylated, downregulated genes. Hypomethylation-upregulated genes were enriched in biological processes of the oxidation-reduction process, cell proliferation, and cell division. Pathway enrichment showed selenocompound metabolism, small cell lung cancer and lysosome. Hypermethylation-downregulated genes were enriched in biological processes of positive regulation of transcription from RNA polymerase II promoter, and cell adhesion. The most significantly enriched pathways involved the transcriptional misregulation in cancer, circadian rhythm, and tight junction. After PPI establishment and survival analysis, seven prognostic hub genes were CKS2, DTL, KIF2C, KPNA2, MYBL2, TPX2 and FBL. Moreover, the most involved hallmarks obtained by GSEA were E2F targets, and G2M checkpoint. Importantly, down-regulated level of KIF2C expression significantly inhibited the proliferative ability and metastasis capacity of SKCM cells. Conclusions: Our study identified potential aberrantly methylated-differentially expressed genes participating in the process of malignant transformation from nevus to melanoma tissues based on comprehensive genomic profiles. Transcription profiles of CKS2, DTL, KIF2C, KPNA2, MYBL2, TPX2 and FBL provided clues of aberrantly methylation-based biomarkers, which might improve the development of precise medicine.